Men's body mass index and infertility - Ruby H.N. Nguyen; Allen J. Wilcox; Rolv Skjærven; Donna D. Baird (2007)
In men, excess weight may be linked with altered testosterone, estradiol levels, poor semen quality and infertility. We investigated whether higher BMI among men is associated with infertility and if so, to what extent that effect might be mediated by altered sexual function. A retrospective cohort study of pregnancies from 1999 through 2005 based within the Norwegian Mother and Child Cohort Study (MoBa). Questionnaires assessed mother's and father's height and weight and time to pregnancy. Our sample comprises 26 303 planned pregnancies. Couples were considered infertile if they took ≥12 months to achieve pregnancy or received infertility treatment. After adjusting for the woman's BMI, coital frequency and the ages and smoking habits of both partners, the odds ratio for infertility was 1.20 for overweight men [BMI 25–29.9; 95% confidence interval (CI) = 1.04–1.38] and 1.36 for obese men (BMI 30–34.9; 95% CI = 1.13–1.63) relative to men with low-normal BMI (20.0–22.4). When BMI was divided into eight categories, there was a trend of increased infertility with increased male BMI. The effect of men's BMI was nearly identical when coital frequency was not included indicating that the effect is not mediated by sexual dysfunction in heavier men. This study adds further support that men with excess body weight are at increased risk of infertility. Values may be underestimated because the most severe cases, couples who do not conceive, are not included in this birth cohort. Research is needed to see if weight loss improves fertility for these men.